2017
DOI: 10.1144/sp456.9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in sediment lithology and sedimentary processes along the Japan Trench: use of deep-sea turbidite records to reconstruct past large earthquakes

Abstract: Large earthquakes and related tsunamis serve as triggering mechanisms that generate turbidity currents which form turbidites. The event deposits from the recent 2011 Tohoku-oki earthquake and tsunami are observed throughout a wide area along the Pacific coast of Tohoku, northern Japan, extending from the coast through the shelf and slope, to the trench floor. Spatio-temporal correlation of turbidites and other tsunamigenic deposits, such as those generated in the 2011 event, can be used to reconstruct the recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 70 publications
6
44
0
Order By: Relevance
“…The AD 1454 M w ≥8.4 Kyotoku (Sawai et al, 2015) and AD 869 M w ≥8.6 Jogan earthquakes (Sawai et al, 2012;Namegaya and Satake, 2014) are modeled to occur offshore Miyagi Prefecture. Ikehara et al (2016Ikehara et al ( , 2018 and Bao et al (2018) reported thick event deposits from sediment cores along the central Japan Trench that are linked to the AD 2011 Tohoku-oki, AD 1454 Kyotoku, and AD 869 Jogan earthquakes. Similarly large earthquakes older than these events have also been documented from widespread tsunami deposits (Satake, 2015) and marine sediments on the mid-slope terrace (Usami et al, 2018).…”
Section: Historically Documented Large Earthquakesmentioning
confidence: 99%
See 2 more Smart Citations
“…The AD 1454 M w ≥8.4 Kyotoku (Sawai et al, 2015) and AD 869 M w ≥8.6 Jogan earthquakes (Sawai et al, 2012;Namegaya and Satake, 2014) are modeled to occur offshore Miyagi Prefecture. Ikehara et al (2016Ikehara et al ( , 2018 and Bao et al (2018) reported thick event deposits from sediment cores along the central Japan Trench that are linked to the AD 2011 Tohoku-oki, AD 1454 Kyotoku, and AD 869 Jogan earthquakes. Similarly large earthquakes older than these events have also been documented from widespread tsunami deposits (Satake, 2015) and marine sediments on the mid-slope terrace (Usami et al, 2018).…”
Section: Historically Documented Large Earthquakesmentioning
confidence: 99%
“…The core locations were carefully determined with the help of bathymetry and onboard initial SBP data interpretation during these cruises. Core processing and analyses followed the same core description and investigation methods (including visual core description, radiograph image analyses, and multi-sensor core logging) to identify thick sedimentary events deposits as used by previous studies (Ikehara et al, 2016(Ikehara et al, , 2018Strasser et al, 2017;Bao et al, 2018;Kioka et al, 2019).…”
Section: Sediment Cores and Radiocarbon Dating Of Background Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Towada Hachinohe (To-H) (Hayakawa, 1985;Ikehara et al, 2017). Bourne et al (2016) 192 report ash from the To-H eruption in the Greenland ice cores which offers the most precise 193 age estimate (Table 1).…”
Section: Introduction 37mentioning
confidence: 99%
“…There are three chapters relating to tsunami studies in Japan: Wallis et al (2017) investigate geological studies in tsunami research since the 2011 Tohoku earthquake; Goda et al (2017) present tsunami simulations of a wide range of realistic slip distribution and kinematic rupture processes, reflecting the current best understanding of what might happen due to a future mega-earthquake at the Nankai-Tonankai Trough; and Ikehara et al (2017) give an overview of spatial variability in sediment lithology and sedimentary processes along the Japan Trench, which can be used to reconstruct the recurrence history of large earthquakes and tsunamis.…”
mentioning
confidence: 99%